Service provision process scheduling using quantum annealing for technical product-service systems - Yi, Li; Wu, Xiangqian; Werrel, Max; Schworm, Philipp; Wei, Wei; Glatt, Moritz; Aurich, Jan C. (Procedia CIRP, 2023)
Service provision processes in technical product-service systems (PSS) should be scheduled before they are performed according to the real process conditions. Incorrectly scheduled service provision processes will result in value losses for both customers and providers of PSS. We developed a quantum annealing (QA)-based service provision process scheduling approach and implemented it in a case study in the commercial vehicle industry. For small-size problems, the results show that our QA-based method delivers comparable results to the conventional computational method. For large-size problems, our QA-based method outperforms the conventional method in terms of computational efficiency and optimization accuracy.